2021
DOI: 10.1044/2021_aja-20-00141
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Speech Recognition Outcomes in Younger and Older Adults With Cochlear Implants

Abstract: Purpose Meta-analyses were conducted to compare pre- to postoperative speech recognition improvements and postoperative scores after cochlear implantation in younger (< 60 years) and older (> 60 years) adults. Method Studies were identified with electronic databases and through manual search of the literature. In the primary analyses, effect sizes between pre- and postoperative scores for each age group were calculated using a formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
2
7
0
Order By: Relevance
“…As discussed in Lambriks et al 1 , it can be argued that the absolute learning speed with either setting will be slower with this approach because the exposure is distributed over twice the amount of time. However, the final performance of our patients was in line with clinical populations, indicating that learning curves were not negatively influenced [17][18][19] . Possibly, selection bias might have occurred in our study population, as subject characteristics could potentially be different within the sample population that was willing to participate in the study compared to the clinical population.…”
Section: Practical Implications For Auditory Neurosciencesupporting
confidence: 68%
“…As discussed in Lambriks et al 1 , it can be argued that the absolute learning speed with either setting will be slower with this approach because the exposure is distributed over twice the amount of time. However, the final performance of our patients was in line with clinical populations, indicating that learning curves were not negatively influenced [17][18][19] . Possibly, selection bias might have occurred in our study population, as subject characteristics could potentially be different within the sample population that was willing to participate in the study compared to the clinical population.…”
Section: Practical Implications For Auditory Neurosciencesupporting
confidence: 68%
“…It is noteworthy that although older adults appear to have poorer neural functioning than middle-aged and young adults (likely attributable to poorer neural survival), older adults receive similar benefit from cochlear implantation to their younger counterparts (3), and many obtain comparable speech recognition outcomes (4,5). This suggests that there must be robust neuroplasticity at higher levels of the auditory system to help these recipients overcome poorer peripheral processing.…”
Section: Discussionmentioning
confidence: 99%
“…Older cochlear implant (CI) recipients tend to have poorer speech recognition than their younger counterparts (1)(2)(3), although this finding is not unanimous (4,5). Age-related difficulties in speech recognition are likely due to changes in cognitive processing, peripheral auditory, and/or central auditory processing (e.g., [6]).…”
Section: Introductionmentioning
confidence: 99%
“…To systematically analyze the efficacy of CIs by considering differences in the characteristics of the studies, a meta-analysis including multiple studies could offer an alternative approach, although few such studies have been reported to date. However, even previously reported meta-analyses have primarily focused on comparing hearing-related abilities, such as speech perception, before and after CIs [ 14 , 28 ]. Very recently, a study investigating changes in cognitive function was published [ 29 ]; however, the number of studies included in the analysis was quite small (seven), and the analysis was based on limited cognitive tests.…”
Section: Introductionmentioning
confidence: 99%